My Myanmar years : a diplomat's account of India's relations with the region - Malik, Preet (New Delhi SAGE Publications, 2016)
"The Indian legendary texts call it Suvarna Bhumi or the Golden Land; its colonial masters called it Burma and its military government renamed it as Myanmar. Whatever the name might be, the country has long been in India's cultural, historical and political consciousness. Essentially a foreign policy document, this book deals in detail with the geostrategic importance and relevance of Myanmar to India's Look East Policy, as narrated by India's ambassador to Myanmar during 1990-1992. It is partly anecdotal and partly historical in nature, providing a first-hand account of Myanmar's political turbulence and India's changing policies under three different governments"--Provided by publisher.
Foreword / by M. Hamid Ansari -- Introduction -- A rough landing : 1990 -- Let's go to history first -- The rice bowl of the British Empire -- Burma, the hermit republic! -- From Nehru to Rajiv -- Of mistrust, mutual discord and disenchantment -- The security issue and the Indian approach in 1992 -- China in between India and Myanmar : 1991-1992 -- Thawing of relations : 1992-2010 -- Getting closer, but not claustrophobic -- Developments after 2008 Constitution -- Myanmar in the post-2010 election period -- The position of the ethnic minorities -- Internal conflict and the security issue -- The bigger brother : China in Myanmar -- China-Myanmar relations : 1948-1988 -- India-China-Myanmar matrix : post-1988 -- President Thein Sein and the changing face of Myanmar -- The economic future of Myanmar -- Of Burma's past and Myanmar's future -- Conclusion -- Annexures.
Includes bibliographical references (pages 229-231) and index.
Keywords: Malik, Preet; Ambassadors -- India -- Biography; Political geography -- Burma